Spaced Scenario Demonstrations Improve Knowledge and Confidence in Pediatric Acute Illness Management - Ojha, Rahul; Liu, Anthony; Champion, Bernard Linton; Hibbert, Emily; Nanan, Ralph Kay Heinrich (Frontiers in Pediatrics, 2014)
ABSTRACT Objectives Nationally accredited simulation courses such as Advance Paediatric Life Support (APLS) and Pediatric Advance life support (PALS) are recommended for health care professionals (HCPs) at 2 yearly intervals as a minimum requirement, despite literature evidence suggesting rapid decline in knowledge shortly after course completion. The objective of this study was to evaluate an observation-based, educational intervention program aimed at improving previously acquired knowledge and confidence in managing critical illnesses. Methods A prospective cohort longitudinal study was conducted over a 6 month period. Participants were assessed with a knowledge based questionnaire immediately prior to and after observing 12 fortnightly critical illness scenario demonstrations (CISD). The outcome measure was performance on questionnaires. Regression analysis was used to adjust for potential confounders. Questionnaire practice effect was evaluated on 30 independent HCPs not exposed to the CISDs. Results Fifty-four HCPs (40 doctors and 14 nurses) participated in the study. All participants had previously attended nationally accredited simulation courses with a mean time since last attendance of 1.8 ± 0.4 years. The median number of attendances at CISD was 6 [2-12]. The mean questionnaire scores at baseline (17.2/25) were significantly lower than the mean post intervention questionnaire scores (20.3/25), p=0.003. The HCPs self-rated confidence in managing CISD was 6.5 times higher at the end of the program in the intervention group (p=0.002) than at baseline. There was no practice effect for questionnaires demonstrated in the independent sample. Conclusions The educational intervention program significantly improved the knowledge and confidence of the participants in managing paediatric critical illnesses. The CISD program provides an inexpensive, practical and time effective method of facilitating knowledge acquisition and retention. Despite the dis